Electronic government in Colombia: A regulatory framework and the assessment of three strategic indexes (2015)
This study presents a review of the regulatory framework dealing with modernization of the State and Electronic Government in Colombia, from 1995 until the present, and assessment of its development according to international criteria, using three indexes for the 2003-2013 period: a) The Index of Electronic Government from the United Nations; b) the Networked Readiness Index from the World Economic Forum; and c) The Index of Perception of Corruption and International Transparency. To analyze the tendencies in these indexes, linear regression, relative and quartile positions were employed. Results made it possible to show a constant evolution of the regulatory framework. Assessment of the indexes is not conclusive. Although Colombia has positive ratings in terms of human capital stock and a high Web presence by the Government, it is essential to advance in technological infrastructure and work around the perception of corruption by the citizenry. © 2015, Universidad del Zulia. All rights reserved.